THE EFFECT OF GOOD CORPORATE GOVERNANCE, LEVERAGE AND COMPANY SIZE ON PROFIT MANAGEMENT - Lindawati, Mrs (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
This study aims to determine the effect of Good Corporate Governance (GCG) proxied through Manjerial Ownership (KM), Board of Directors Size (UDD), and Board of Commissioners Size (UDK), Leverage and Company Size, on property companies listed on the IDX. To facilitate research, the author uses financial statements as a sample of 10 property companies in the period 2011-2017. The research method used is quantitative. The analytical method used in this study is panel data analysis. The results showed that KM did not significantly influence earnings management, UDD had a significant effect on earnings management, UDK had no significant effect on earnings management, GCG had a significant effect on earnings management, Leverage had no significant effect on earnings management, Company Size had a significant effect on earnings management. Based on the simultaneous test showing GCG, Leverage, and Company Size simultaneously have a significant effect on earnings management.